Quraish Shihab and Buya Hamka: The Concept of Multicultural Education from a Qur'anic Perspective - Putri, Lusiana Rahmadani; Vera, Awada; Visconte, Arda (International Journal of Educational Narratives, 2023)
Background. This thesis article describes a concept of multicultural education from the perspective of the Qur’an in Qs. Al-hujurat verse 13 from the work of Quraish Shihab and Buya Hamka. Purpose. This research aims to analyze gradually by using data collection, data reduction, data presentation, and conclusions. Method. This thesis uses the literature method, researchers also use the comparative method and the approach of the theory of meaning and understanding by Jorce Gracia to facilitate understanding of the meaning of multicultural education contained in Qs. Al-Hujurat verse 13 in the tafsir by Quraish Shihab and Hamka. Results. The results show that Quraish Shihab's work on multicultural education design is due to the recognition of culture and differences as sunatullah. Humans must recognize egalitarianism (equality of human degrees), brotherhood (ukhuwah), mutual help, and know each other. Multiculturalism is also found in the Qur'an surah Al-Hujurat verse 13 according to Hamka, including al-musawah (equality), ukhuwah (brotherhood), ta'aruf (knowing each other), and tasamuh (tolerance). Differences in interpreting Qs. Al-hujurat about multicultural education in the tafsir Al-misbah and tafsir Al-azhar, in the book Tafsir Al-Misbah by Quraish Shihab further explains that multicultural education is an understanding of a person who recognizes the diversity and comparison of sunatullah. Conclusion. In conclusion, it is very important for madrasah principals to improve the quality of Arabic language learning. Teachers must be qualified because teachers are one of the micro components of the education system in schools. Therefore, it is very important for madrasah principals to improve the quality of Arabic language learning.